A java based visual tool to learn CPU scheduling algorithms - Jain, Neetu; Suresh, P. V. (INDIACom : 2014 International Conference on Computing for Sustainable Global Development : 5-7 March 2014, 2014)
CPU scheduling algorithms are integral part of learning operating system. Over the years, it has been experienced that initially CS students face a lot of problems in understanding and further implementing the various scheduling algorithms. Also generating and regenerating Gantt Charts is faced with difficulties by many CS students. A visual tool or diagram has always been effective way in better learning and understanding. We developed a Java and Java Swing based application, to visually explain various scheduling algorithms. User can enter the runtime details of processes and the tool is capable of graphically showing the execution of processes inside the system using a particular scheduling algorithm. The tool is also capable of doing calculations different effectiveness criteria of an algorithm like waiting time of each process, average waiting time and turnaround time. Proposed tool has used different colors to depict processes to have much better understanding of the operations inside the system.